Eco-Friendly Demersal Fish Trawling Systems - R.P., Mounsey; J., Prado (Fishery Technology, 2025)
Trawling has impacts on the seabed when various elements of bottom rigging, particularly the trawl boards and goundrope, skip ub or dig into the substrate. Trawl fishermen rig their gear to efficiently sweep the seabed which results in the destaiction of marine organisms or change the substrate. In northern Australian fork rigged semi-pelagic trawl system has been developed which was found compatible with that of a standard similarly sized demersal trawl system. Although this system had significantly less impact on the substrate, and produced a higher quality product,fishermen found it difficult to operate.Consequently the original standard demersal trawl system was then slightly modified in order to achive similar results.The modified system has proven its commercial viability in Australia’s tropical seas.The ongoing reserch is now focussing on further simplifying the standard system with a possible cross-over board to net,bridle arrangement.This paper describes the three systems,includeing the general rigging arrangements and net designs.